2004
DOI: 10.1016/s0378-1097(03)00960-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired host defense to infection and Toll-like receptor 2-independent killing ofBorrelia burgdorfericlinical isolates in TLR2-deficient C3H/HeJ mice

Abstract: To investigate the role of Toll-like receptor 2 (TLR2)-mediated signaling in host innate defense and development of Lyme disease, the pathogenicity of Borrelia burgdorferi sensu stricto clinical isolates representing two distinct genotypes (RST1 and RST3A) was assessed in TLR2 3=3 C3H/HeJ mice. All TLR2 3=3 mice infected with a B. burgdorferi RST1 isolate developed severe arthritis. The numbers of spirochetes in heart, joint and ear biopsy specimens were significantly higher in TLR2 3=3 mice than in wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…These data support our findings that this SNP affects the recognition of triacylated, but not diacylated stimuli, because triacylated lipoproteins were described in Mycobacterium tuberculosis (42,43), while LTA from S. aureus is diacylated (31). Our finding that Arg753Gln protects from clinical symptoms of late stage infection with B. burgdorferi, including Lyme arthritis, appears to be in contrast to studies investigating TLR-2 and MyD88 knockout mice, because these animals displayed more severe arthritis than the corresponding wt mice (17)(18)(19)44), and mice heterozygous for TLR-2 did not differ from wt mice (17). However, arthritis in mice experimentally infected with B. burgdorferi is considered to be a subacute stage of disease, comparable to meningoencephalitis or myocarditis in humans, in which bacteria are present in the tissues, and we did not observe any association of subacute stages of LD with TLR-2 SNPs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These data support our findings that this SNP affects the recognition of triacylated, but not diacylated stimuli, because triacylated lipoproteins were described in Mycobacterium tuberculosis (42,43), while LTA from S. aureus is diacylated (31). Our finding that Arg753Gln protects from clinical symptoms of late stage infection with B. burgdorferi, including Lyme arthritis, appears to be in contrast to studies investigating TLR-2 and MyD88 knockout mice, because these animals displayed more severe arthritis than the corresponding wt mice (17)(18)(19)44), and mice heterozygous for TLR-2 did not differ from wt mice (17). However, arthritis in mice experimentally infected with B. burgdorferi is considered to be a subacute stage of disease, comparable to meningoencephalitis or myocarditis in humans, in which bacteria are present in the tissues, and we did not observe any association of subacute stages of LD with TLR-2 SNPs.…”
Section: Discussionsupporting
confidence: 85%
“…The causative role of IFN-␥ production for the development of arthritis in LD is in line with our hypothesis that lower levels of this and other cytokines protect from late stage LD, while acute and subacute stages are not affected. Furthermore, one study showed that, while arthritis was enhanced in TLR-deficient mice, carditis was less severe, indicating that an impaired recognition of B. burgdorferi may also have beneficial effects on the course of infection in these animals (44).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of selected cytokine and related genes in mouse tissue and in RAW264.7 cells exposed to either isolate B356 or isolate BL206 was determined by real-time quantitative RT-PCR using SYBR Green technology with the LightCycler (Roche Applied Science) or the ABI 7900HT SDS (Applied Biosystems), as described previously (10,34,36). For each RNA sample, the expression of ␤-actin was quantified by real-time RT-PCR, and a ⌬⌬C t method was used to estimate the differential gene expression between samples (37).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…Spirochetal outer surface lipoproteins signal through TLR1/TLR2 heterodimers in a CD14-dependent manner, generating inflammatory mediators in Lyme disease patients, human monocytic cells, primate glial cells, mice and murine monocytes (12, 20 -26). TLR2 also functions in host defense, as TLR2 Ϫ/Ϫ mice harbor higher spirochete burdens in target tissues than wild-type controls (27,28). Recent reports have also established a role for TLR5, a receptor for bacterial flagellin, as a mediator of B. burgdorferi-induced inflammation in murine cells (12,25).…”
mentioning
confidence: 99%